Fatty Pancreas Is a Risk Factor for Pancreatic Cancer A Systematic Review and Meta-Analysis of 2956 Patients - Lipp Mónika Bernadett; Tarján Dorottya; Lee Jimin; Zolcsák Ádám; Szalai Eszter; Teutsch Brigitta; Faluhelyi Nándor; Erőss Bálint Mihály; Hegyi Péter; Mikó Alexandra (2023)
Pancreatic cancer (PC) is one of the most lethal cancers worldwide. Recently, fatty pancreas (FP) has been studied thoroughly, and although its relationship to PC is not fully understood, FP is suspected to contribute to the development of PC. We aimed to assess the association between PC and FP by conducting a systematic review and meta-analysis. We systematically searched three databases, MEDLINE, Embase, and CENTRAL, on 21 October 2022. Case-control and cross-sectional studies reporting on patients where the intra-pancreatic fat deposition was determined by modern radiology or histology were included. As main outcome parameters, FP in patients with and without PC and PC in patients with and without FP were measured. Proportion and odds ratio (OR) with a 95% confidence interval (CI) were used for effect size measure. PC among patients with FP was 32% (OR 1.32; 95% CI 0.42-4.16). However, the probability of having FP among patients with PC was more than six times higher (OR 6.13; 95% CI 2.61-14.42) than in patients without PC, whereas the proportion of FP among patients with PC was 0.62 (95% CI 0.42-0.79). Patients identified with FP are at risk of developing PC. Proper screening and follow-up of patients with FP may be recommended.
Keywords: Klinikai orvostan